Green engineering of cellulose nanofibers and nanopapers from Wodyetia bifurcata fruits: a sustainable approach with emphasis on process optimization and tensile property assessment - Sankar, Sameera; Neenu, K. V.; Parameswaranpillai, Jyotishkumar; Ajithkumar, T. G.; Shelke, Ankita Ramesh; Begum, P. M. Sabura; Bipinbal, P. K.; George, Tresa Sunitha; Badawi, Michael; Dominic, Midhun (Biomass Conversion and Biorefinery, 2025)
Nanocellulose emerges as a highly promising material with versatile applications, offering solutions to environmental and sustainability challenges. This study delves into the extraction of cellulose nanofibers (CNFs) from Wodyetia bifurcata fruit pulp through mild oxalic acid hydrolysis assisted by steam explosion. To ensure environmental compatibility, chlorine-free pre-treatments were applied to eliminate non-cellulosic components. Chemical composition analysis verified the effective removal of non-cellulosic elements, validated by Fourier transform infrared spectroscopy (FTIR). Solid-state 13C nuclear magnetic resonance (13C NMR) spectroscopy confirmed the presence of type I cellulose α-polymorph in the CNF, while a crystallinity index of 60% was determined by X-ray diffraction analysis (XRD). The transmission electron microscopy (TEM) images revealed a fibrous morphology with a fiber diameter ranging from 9 to 36 nm. Dynamic light scattering (DLS) was employed to corroborate the observed fiber diameter. Mild acid hydrolysis elevated the maximum degradation temperature (Tmax) of CNF to 39 °C compared to the pristine sample. Furthermore, this research explores the application of CNFs in nanopaper development using a casting method. The resulting nanopapers exhibited a tensile strength of ~ 17 MPa and a transmittance of 25%. These nanopapers present a viable pathway toward eco-friendly products in various industries, promising to revolutionize upcoming sustainable packaging technologies.